إزالة الفوسفور من مياه صرف مخابر مرفأ اللاذقية - جناد, هيثم; ساتيك, سينا (Latakia University Journal -Engineering Sciences Series, 2017)
تهدف هذه الدراسة إلى دراسة فعالية كل من (كلوريد الحديد, الرماد, تفل القهوة) في إزالة الفوسفور من مياه صرف مخابر مرفأ اللاذقية التي يتم تجميعها في حفرة تفتيش منفصلة, وتم إجراء تجارب مخبرية على مياه تحوي تراكيز عالية من الفوسفور سواء أكانت مياه صرف حقيقية أو محاليل عيارية من أوكسيد الفوسفور المخبري. حيث تم تجريب كلوريد الحديد عند جرعات FeCl3/P=(0-5) كمعدل وزني ليعط نسب فعالية %(-8070) بما يتوافق مع قيمة الـ pH وتم تحديد زمن إعادة تحرر الفوسفور بعد10 - 12) ) ساعة من بدء الترسيب, كما تم تجريب الرماد كعامل ممتز بجرعات Ash/P=(2-4.5) كمعدل وزني لتعط نسب فعالية وصلت إلى 98% ولوحظ إعادة تحرر الفوسفور بعد 11 ساعة مع تحديد قيم الـpH الموافقة لذلك, أما تفل القهوة فعند إضافته بجرعات Coffee dreg/P =(3-10) كمعدل وزني حقق نسبة إزالة تتراوح % (40 - 99) وعاد للتحرر بعد 24 ساعة وبنتيجة هذه التجارب تم اقتراح الحل الأمثل من الناحية الاقتصادية بالنسبة لحالة الدراسة.This research aims to study the effectiveness of each(ferric chloride , ash and coffee dregs) to remove phosphorus from Lattakia Port Laboratories' waste water which is assembled in a separate sewage pit by doing laboratory experiments on water containing high concentrations of phosphorus, whether real wastewater or standard solutions of phosphorus oxide. Where it has been experimenting with ferric chloride at doses as weight average(FeCl3/P = (0-5)) to give effectiveness ratios(70- 80)% with determining the value of the pH-compliant and it was noted re-releasing of phosphorus time after(10-12) hours of the start of precipitation, beside that it has been experimenting with ash as adsorpted agent at doses as weight average(Ash/P = (2-4.5)) to give effectiveness ratio which it had reached to 98% where it was noted re-releasing of phosphorus after 11 hours with determining the pH values of approval for that, As coffee dregs when added in doses)Coffee dreg/P = 3-10) as weight average, it fulfilled proportion removal(40 - 99) % and phosphorus re-released after 24 hours. The outcome of these experiments was to propose the most appropriate economic solution in the case of study.